Hubungan Panjang-Bobot dan Faktor Kondisi Ikan Estuarine Glass Perch (Ambassis macracanthus Bleeker, 1849) di Perairan Taman Hutan Raya (Tahura) Ngurah Rai, Teluk Benoa, pada Musim Timur - Franceska Kendra Rossa S; Nyoman Dati Pertami; I Nyoman Giri Putra (Journal of Marine Research and Technology, 2023)
The growth aspect is important in determining fish well-being in an area. However, research on the growth aspect of Ambassis macracanthus Bleeker, 1849, in Ngurah Rai Forest Park has never been conducted This study aims to determine the length-weight relationship and condition factor of A. macracanthus as well as to evaluate the water condition in Ngurah Rai Forest Park, Benoa Bay during the east season. The sample was collected applying descriptive and quantitative methods, whilst the purposive sampling method was used to take the samples from three stations using Bubu and experimental gill net. During the sampling collection process, 304 fish individuals were caught by the experimental gill net at station 1 (Serangan waters). Based on the analysis between the length and weight relationship of A. macracanthus, the equation of W=0,024L2.38, where from this equation, the value of b = 2.38 is obtained. Through the T-test, the value of b < 3 showed a negative allometric growth pattern; namely, the growth in length is more dominant than the increase in weight. The average relative condition factor increased monthly, with the highest value of 1.37 in August. However, the value of the relative condition factor indicates that the fish in Tahura waters are thin (Kn < 2). In general, the temperature and dissolved oxygen of Ngurah Rai Forest Park waters are not following quality standards.